Vascular comorbidity is associated with lower brain volumes and lower neuroperformance in a large multiple sclerosis cohort. (October 2021) - Fitzgerald, Kathryn C; Damian, Anne; Conway, Devon; Mowry, Ellen M
Objective: The objective of this study is to assess the association between vascular comorbidity burden with clinical and imaging features of disease burden in a large population of people with multiple sclerosis (MS). Methods: We included participants from the MS Partners Advancing Technology Health Solutions (MS PATHS) cohort. We evaluated if vascular comorbidities (diabetes, hypertension, and dyslipidemia) or a composite sum of comorbidities was associated with MS characteristics, including objective neurologic function assessments and quantitative brain magnetic resonance imaging (MRI) measurements in propensity score–weighted models. Results: In total, 11, 506 participants (6409 (55%) with brain MRI) were included. Individuals with 2+ vascular comorbidities had slower walking speed (standard deviation (SD) = −0.49; 95% confidence interval (CI) = −0.78, −0.19; p = 0.001), slower manual dexterity (SD = −0.41; 95% CI = −0.57, −0.26; p < 0.0001), and fewer correct scores on cognitive processing speed (SD = −0.11; 95% CI = −0.20, −0.02; p = 0.02) versus those with no comorbidities. Those with 2+ had lower brain parenchymal (−0.41%, 95% CI = −0.64, −0.17) and gray matter fractions (−0.30%, 95% CI = −0.49, −0.10), including reduced cortical (−10.10 mL, 95% CI = −15.42, −4.78) and deep (−0.44 mL, 95% CI = −0.84, −0.04) gray matter volumes versus those with no comorbidity. Conclusion: Increased vascular comorbidity burden was associated with clinical and imaging markers of neurologic dysfunction and neurodegeneration in MS. Strategies to optimize comorbidity management in people with MS are warranted.